Mick Harte was here - Park, Barbara (New York : Knopf : Distributed by Random House, 1995)
Thirteen-year-old Phoebe recalls her younger brother Mick and his death in a bicycle accident.
"Apple soup books."
730
Accelerated Reader AR
Keywords: Brothers and sisters -- Fiction; Death -- Fiction